Membangun Identitas Merek Yang Kuat: Strategi Hyundai Dalam Industri Otomotif Indonesia - Agung Wirakusuma; Tombang Daulat Ni Roha Harianja; Mohamad Zein Saleh (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study examines Hyundai's marketing strategies in building a strong brand identity in the Indonesian automotive industry. The automotive industry in Indonesia is highly competitive, requiring companies to establish strong brand identities to gain the largest market share and customer loyalty. Hyundai, as a leading brand in the automotive industry, needs to build a strong brand identity to compete effectively. Strong brand identities can establish emotional connections with consumers, create sustainable brand recognition, and become valuable assets that differentiate Hyundai from competitors. Building a strong brand identity involves various elements such as logos, colors, typography, and even sound. Additionally, content on social media is a powerful tool in this strategy. Relevant, useful, and engaging content can help establish authority in the industry and attract potential customers. However, companies must be cautious not to mimic competitors' brand identities and apply online and offline content inconsistently. Moreover, companies need to ensure that brand identities are built sustainably and align with the values they want to convey. Thus, the background of the title "Building a Strong Brand Identity: Hyundai's Strategy in the Indonesian Automotive Industry" emphasizes the importance of building a strong brand identity in the competitive automotive industry and how Hyundai can apply this strategy in the Indonesian market.